2008
DOI: 10.1021/nn800509b
|View full text |Cite
|
Sign up to set email alerts
|

Single-Molecule Detection of Human Topoisomerase I Cleavage−Ligation Activity

Abstract: In the present study, we demonstrate the conversion of a single human topoisomerase I mediated DNA cleavage-ligation event happening within nanometer dimensions to a micrometer-sized DNA molecule, readily detectable using standard fluorescence microscopy. This conversion is achieved by topoisomerase I mediated closure of a nicked DNA dumbbell structure, followed by rolling circle amplification. The resulting product consists of multiple tandem repeats of the DNA dumbbell and can subsequently be visualized by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
110
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(115 citation statements)
references
References 40 publications
1
110
1
Order By: Relevance
“…1999; Husain et al, 1994). Since a comparison of the TOP1 activity in the tumor and adjacent non-tumor tissue has not been performed in NSCLC we measured TOP1 activity in the cryosection extracts also used for TDP1 measurement using our previously published TOP1 nanosensor (Stougaard et al, 2009). We found that there was a significantly (p = 0.0038) higher activity of TOP1 in the tumor samples compared to the non-tumor samples (Fig.…”
Section: Top1 Activity In Nsclcmentioning
confidence: 89%
See 2 more Smart Citations
“…1999; Husain et al, 1994). Since a comparison of the TOP1 activity in the tumor and adjacent non-tumor tissue has not been performed in NSCLC we measured TOP1 activity in the cryosection extracts also used for TDP1 measurement using our previously published TOP1 nanosensor (Stougaard et al, 2009). We found that there was a significantly (p = 0.0038) higher activity of TOP1 in the tumor samples compared to the non-tumor samples (Fig.…”
Section: Top1 Activity In Nsclcmentioning
confidence: 89%
“…Using our previously developed nanosensors capable of measuring the specific activities of TOP1 (Stougaard et al, 2009) and TDP1 (Jensen et al, 2013) we examined the activities of TOP1 and TDP1 in cryosections from 24 paired (tumor and adjacent non-tumor) NSCLC tissues. We found that both TOP1 and TDP1 were upregulated in the tumor tissue compared to the adjacent non-tumor tissue in NSCLC.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
See 1 more Smart Citation
“…Detection of enzyme activities via DNA nanosensors usually takes advantages of the functionality of DNA-modifying enzyme, such as DNA cleavage, ligation, synthesis and repair [15]. For example, specific and sensitive measurements of the cleavage-religation activities from the DNA topoisomerase and the tyrosine recombinase families have previously been demonstrated, by combining DNA nanosensors with rolling circle amplification [16,17]. Even though this assay enables a single molecular sensitivity, the highly delicate fluorescence microscope and the time-consuming procedures have limited its applicability for point-of-care settings.…”
Section: Why Dna-modifying Enzymes?mentioning
confidence: 99%
“…Hence, besides the obvious interest to basic science there is a growing interest for biosensors capable of detecting the specific action of enzymes in complex biological samples such as crude cell extracts used for clinical applications. In line with this demand we have previously developed DNA-based biosensors capable of detecting the specific activity of human topoisomerase I (TopI), and the two related enzymes, Flp-and Cre recombinases, in crude cell extract Stougaard et al, 2009). These biosensors relied on rolling circle amplification (RCA) and allowed highly sensitive and quantitative detection of enzyme activities at the level of single catalytic events even in single cells .…”
Section: Introductionmentioning
confidence: 99%